MARKETING ANALYSIS OF ARWOOD IN LOMBOK ISLAND - Eka Nurminda Dewi Mandalika (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
This study aims to determine the marketing channel and the efficiency level of marketing of gaharu on Lombok Island. This research was conducted in four regions: West Lombok Regency, North Lombok Regency, Central Lombok Regency, and Mataram City. The respondents consisted of four people: three district-level collectors and one exporter. Determining marketing agency respondents is done using the